Doege– Potter syndrome due to endothoracic solitaryhypoglycemic fibrous tumor - Lopez- Hinostroza, Madaleine (2022)
Doege–Potter syndrome leads to severe and sustained symptomatic hypoglycemia and is associated with the solitary fibrous tumor. It is a rare cause, and its diagnosis requires a clinical suspicion and other markers such as insulin-like growth factor II. Here, we describe a case of a patient with intrathoracic tumor and hypoglycemia.